Exterior Indicators and Body Conformation Indices of Jongeldi-Type Black Karakul Lambs in Different Age Groups - Maxammatova, D.; Turanov, M. (American Journal of Botany and Bioengineering, 2025)
The article presents the results of a study of the body condition indices of black Karakul lambs of the Dzhangeldinsky breeding type.